Influence of nutrition claims on different models of front-of-package nutritional labeling in supposedly healthy foods: Impact on the understanding of nutritional information, healthfulness perception, and purchase intention of Brazilian consumers - Prates, Sarah Morais Senna; Reis, Ilka Afonso; Rojas, Carlos Felipe Urquizar; Spinillo, Carla Galvão; Anastácio, Lucilene Rezende (Frontiers in Nutrition, 2022)
Nutrition claims are positive information on foods that are widely used as a marketing strategy on labels. On the other hand, front-of-package nutritional labeling (FoPNL) aims to make it easier for consumers to understand the nutritional composition of foods and favor healthy food choices. However, the concomitant presence of nutrition claims and FoPNL may hinder the understanding, judgment and choices of consumers at the moment of purchase. Therefore, the objective of this study was to evaluate the influence of nutrition claims on the efficacy of FoPNL models on the understanding of nutritional information, healthfulness perception and purchase intention of Brazilian consumers. It was an experimental, cross-sectional study, carried out using an online questionnaire, with a total of 720 participants, randomly divided into four FoPNL conditions: control, octagon, triangle and magnifying glass. Each participant looked at 12 food packages, which were produced following the factorial design: (i) food category (cereal bar, whole grain cookies and snacks); (ii) product type (one critical nutrient x two critical nutrients) and (iii) nutrition claims (present x absent). The comprehension of nutritional information was evaluated through the identification of excessive nutrients, and the healthfulness perception and purchase intention were evaluated on a 7-point scale. The results indicated that the presence of FoPNL increased the understanding of the information and reduced healthfulness perception and purchase intention. The presence of nutrition claims influenced the three results independently, decreasing the probability of understanding information about food composition by 32%, and increasing the probability of participants perceiving the product as healthy by 89% as well as purchase intention by 52%. Nonetheless, the interaction “FoPNL x claims” was not significant, which showed that both pieces of information act independently. All FoPNL models were more effective than control, and the octagon and triangle models were more effective than the magnifying glass one for the results of healthfulness perception and purchase intention. The results prove the efficacy of FoPNL in consumer understanding and judgment. Despite the positive effects of FoPNL it did not cancel the positivity bias generated by the claims.